Balancing profits and conservation: a human environmental impact PBL for upper elementary and middle grades STEM club students. (3rd July 2019) - Hite, Rebecca L.; White, Jill
Abstract: Students require experiences that reflect the difficult decision making found in the real world. A current and future challenge for today's students is understanding the balance between economic pressures and ensuring environmental conservation. Using problem-based learning (PBL) as a pedagogical vehicle, 10 groups of upper elementary students made informed choices in conducting a mining operation near a fictional coastline with diverse flora and fauna, including an endangered species (sea turtles). In this article, we provide a student-led PBL activity of " Balancing Profits and Conservation " used for an after school STEM club for 4th and 5th graders focused on sea turtles and marine education. Game cards and graphic organizers (included in the article) scaffolded the PBL process at each step. Activities include students (1) considering avenues of ecological conservation, (2) developing and executing a mining operation using limited funding (game pieces) and a variety of tools, (3) extracting resources from a simulated environment to ascertain profit, (4) reflecting on, assessing and remediating the environmental impact, and (5) communicating their outcomes to peers. Students' end of project presentations elucidated the successes and challenges of their chosen mining plan, both in implementation and consequences. This activity may be used in in/formal environmental education.